Mathematics for the environment - Walter, Martin E. (Martin Edward) (Chapman & Hall/CRC Press, 2011)
Walter (U. of Colorado-Boulder) proposes a course on mathematics and environmental issues as an alternative to such courses as college algebra, liberal arts math, and so on for undergraduate instruction in the basic mathematical literacy that he argues is required for citizens in a modern democracy to make informed choices. In preparation for such a course, his textbook covers how mathematics is connected to everything; math and nature and the nature of math; one of the oldest mathematical patterns; counting; box models for population, money, and recycling; chance in health, surveillance, spies, and voting; economics; and media literacy.